Realization of the genetic potential of frost hardiness in apple hybrids of different ploidy - N. G. Krasova; Z. E. Ozherelieva; A. M. Galasheva (Вавиловский журнал генетики и селекции)
The results of a study of resistance to unfavorable winter conditions of new selection seedlings of apple developed in the Institute as part of priority directions of apple breeding are presented.The goal of the work is to estimate winter hardiness of apple genotypes developed by combining scab resistance in a triploid genotype (RVi6+3х). Methods of a winter hardiness study in the field and laboratory conditions were used by modelling damage factors in a “ESPEC” PSL-2 KPN deep-freezer . It was determined that by early December the genotypes gained a good hardening and displayed the resistance of vitally important tissues to early winter frosts up to 30 °C (frost resistance component I). The genotypes were revealed that under artificial freezing bore critical temperatures –38 and –40 °C as well as –42 °C with damages of vitally important tissues at the level of Antonovka Obyknovennaya (component II). The modelling of a three-day artificial thaw (+2 °C) with the following temperature lowering to –30 °C showed that in all studied apple seedlings the damages of bark, cambium and wood were reversible and did not exceed 2.0 points while in immune, triploid forms 31-2-130 and ELS 31-36-149, the damages did not exceed 1.2 points. The winter hardiness study of selection apple seedlings allowed revealing the most winter hardy and promising genotypes: scab resistant and triploid forms 31-2-15, 31-2-115, 31-2-130 (Afrodita×13-6-106) and 31-36-149 [Veniaminovskoye×25-35-144 (Wealthy tetraploid× Papirovka tetraploid)] as well as scab resistant diploids 32-35-58 (Yubiley Moskvy×Krasa Sverdlovska) and 31-15-126 [23-16-96 (seedling 814 – open pollination)×Gulliver)]. Those genotypes displayed the resistance of vitally important tissues to early winter frosts, frosts in the middle of winter up to –40 °C at the level of Antonovka Obyknovennaya as well as to the frosts after thaws and retained the ability to restore resistance during repeated hardening after thaws.